Numerical Modeling of Water Movement from Buried Vertical Ceramic Pipes through Soils (Journal of Engineering, 2018)
The problem of water scarcity is becoming common in many parts of the world, to overcome part of this problem proper management of water and an efficient irrigation system are needed.  Irrigation with a buried vertical ceramic pipe is known as a very effective in the management of irrigation water.  The two- dimensional transient flow of water from a buried vertical ceramic pipe through homogenous porous media is simulated numerically using the HYDRUS/2D software.  Different values of pipe lengths and hydraulic conductivity were selected.  In addition, different values of initial volumetric soil water content were assumed in this simulation as initial conditions.  Different values of the applied head were assumed in this simulation as boundary conditions.  The results of this research showed that greater spreading occurs in the horizontal direction.  Increasing applied heads, initial soil water contents and pipe hydraulic conductivities, cause increasing the size of wetting patterns but in a few increases.  Also, the results showed that the empirical formulas which can be used for expressing the wetted width and depth in terms of applied head, initial soil water content, application time, pipe hydraulic conductivity, and pipe length, are good and can be used as design equations.